Exercise tolerance and quality of life in patients with known or suspected coronary artery disease - Katsi, Vasiliki; Georgiopoulos, Georgios; Mitropoulou, Panagiota; Kontoangelos, Konstantinos; Kollia, Zoi; Tzavara, Chara; Soulis, Dimitrios; Toutouzas, Konstantinos; Oikonomou, Dimitrios; Aimo, Alberto; Tsioufis, Konstantinos (Quality of life research, 2021)
Background Coronary artery disease (CAD) is known to impact on patients’ physical and mental health. The relationship between performance on treadmill exercise tolerance test (ETT) and health-related quality of life (HRQL)has never been specifically investigated in the setting of CAD. Methods Consecutive patients undergoing an ETT with the Bruce protocol during a diagnostic workup for CAD ( n = 1,631, age 55 ± 12 years) were evaluated. Exercise-related indices were recorded. Detailed information on cardiovascular risk factors and past medical history were obtained. HRQLwas assessed with the use of the validated 36-Item Short Form Survey (SF-36) questionnaire. Results Increasing age and the presence of cardiovascular risk factors and comorbidities correlated with lower scores on the physical and mental health component of SF-36(all P < 0.05). Subjects with arrhythmias during exercise and slow recovery of systolic blood pressure had lower scores on the physical health indices or the Social Role Functioning component ( P < 0.05). Achieved target heart rate and good exercise tolerance were independently associated with better scores of the physical and mental health domains of SF-36 and overall HRQLscores (β = 0.05 for target HR and PCS-36, β = 1.86 and β = 1.66 per increasing stage of exercise tolerance and PCS-36 and MCS-36, respectively, P < 0.001 for all associations). Ischemic ECG changes were associated with worse scores on Physical Functioning (β = − 3.2, P = 0.02) and Bodily Pain (β = − 4.55, P = 0.026). Conclusion ETT parameters are associated with HRQL indices in patients evaluated for possible CAD. Physical conditioning may increase patient well-being and could serve as a complementary target in conjunction with cardiovascular drug therapy.